Pengelolaan Pembelajaran Pendidikan Anak Usia DiniDi Taman Kanak-Kanak Iman Istiqomah Salatiga - Sukono, Sarwo, Prof. Dr. Sutama, M.Pd, Dr. Samino, M.M (2015)
The purpose of this research is describing (1) planning strategy learning education in ECD Iman Istiqomah Salatiga, (2) teaching education in ECD Iman Istiqomah Salatiga, (3) evaluation learning education in ECD Iman Istiqomah Salatiga. This research is conducted qualitatively with ethnography approach, and there are three techniques to collect the data, they are: (1) deep interview (2 ) observation (3) documentation . The data analysis is conducted in four steps, (1) data collection (2) data reduction (3) data presentation and (4) data verification. The writer uses triangulation of sources technique and member check to test the data validity. The research concludes (1) planning strategy learning education in ECD Iman Istiqomah Salatiga has already been in accordance with reference of the lesson of play group. (2) teaching education in ECD Iman Istiqomah Salatiga is divided into eight centers, and in the learning process refers to the principles of learning by playing. (3) evaluation learning education in ECD Iman Istiqomah Salatiga already to learning early childhood. Learning evaluations activities done in ECD Iman Istiqomah Salatiga consists of three events, namely observation, anecdotes notes and portfolio.